The Negative Feedback Connection in the Homeostatic System of Carbohydrate Exchange Regulation - Sokol, Yevgen I.; Lapta, Stanislav S.; Chmykhova, Oksana V.; Solovyova, Olga I.; Karachntsev, Iurii; Kravchun, Nona; Goncharova, Olga (Institute of Electrical and Electronics Engineers, 2018)
The article gives a brief overview of the state of solution of an important scientific and applied problem of mathematical modeling of the physiological system of carbohydrate exchange regulation. It shows that for the half of the century all the previous attempts to solve it have been physiologically inadequate. It demonstrates the model that has been proposed a little more than twenty years ago and is yet little known to the scientific community, which is the most minimal model of regulation of carbohydrate exchange in the form of the model of the homeostatic self-regulation of the glycemic level for a single variable of the glycemic state at the periphery. This model is structurally-functional in the form of a differential equation of the first order with a delayed argument. It reproduces - without re-adjusting of its main parameters - universally the glycemic curve of both IVGTT and OGTT, as well as the daily glycemic profile. The internal fundamental difference of this model from all the previous models is ascertained in describing the oscillations of glycemic curves due to the different character of the negative feedback connection with delay: the local and integral aftereffect. For the first time the universal equation of oscillations is proposed in the system with self-regulation, which combines both harmonic and nonharmonic oscillations
Keywords: equation; model; glycemia; regulation; delay; aftereffect